Ultradiscrete Painlevé VI with Parity Variables - Takemura, K.; Tsutsui, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
We introduce a ultradiscretization with parity variables of the q-difference Painlevé VI system of equations. We show that ultradiscrete limit of Riccati-type solutions of q-Painlevé VI satisfies the ultradiscrete Painlevé VI system of equations with the parity variables, which is valid by using the parity variables. We study some solutions of the ultradiscrete Riccati-type equation and those of ultradiscrete Painlevé VI equation.